Public Participation and Restoration in Historic Cities. The Case of Zagreb and Dubrovnik, Yugoslavia - Čaldarović, Ognjen (Array, 1991)
In the chapter major sociolgoical concerns and aspects are discussed concerning the historical cores of Zagreb and Dubrovnik. Major approches to restauration of historical cores are presented and major results of sociological researchers concerning these issues are presented.